When work–family guilt becomes a women's issue: Internalized gender stereotypes predict high guilt in working mothers but low guilt in working fathers - Aarntzen, Lianne; Derks, Belle; van Steenbergen, Elianne; van der Lippe, Tanja (British Journal of Social Psychology, 2023)
Les stéréotypes de genre prescrivent aux mères, mais pas aux pères, de donner la priorité à leur famille plutôt qu’à leur travail. Par conséquent, l’intériorisation des stéréotypes de genre peut prédire une culpabilité plus élevée chez les mères que chez les pères dans des situations où ils privilégient leur travail plutôt que leur famille. L’étude 1 (135 mères et 116 pères) a en effet révélé que plus les stéréotypes de genre implicites des pères étaient forts (mesurés à l’aide d’une tâche d’association implicite genre-carrière), moins les pères se déclaraient coupables dans une situation fictive d’interférence du travail dans la famille. Bien que les mères aient en moyenne déclaré une culpabilité plus élevée que les pères, cet effet n’a pas été atténué par leurs stéréotypes de genre implicites. L’étude 2 (étude du journal quotidien auprès de 105 mères) a toutefois révélé des preuves de l’effet modérateur des stéréotypes de genre implicites sur la culpabilité des mères qui travaillent. Plus les stéréotypes de genre implicites des mères étaient forts, plus elles déclaraient avoir des conflits entre le travail et la famille et de la culpabilité les jours où elles travaillaient de longues heures. Ces résultats montrent que les stéréotypes de genre implicites façonnent la façon dont les parents perçoivent leurs choix travail-famille.
Keywords: 2000 à aujourd'hui; 2020-2029; care; charge mentale; conciliation famille-travail; culpabilité; discipline; europe; famille; maternité; pays-bas; projet charge mentale; psychologie; périodes historiques; ressource en ligne; régions géographiques; sciences humaines; stéréotypes de genre; thématiques; travail; émotions

Resisting and conforming to the ‘lesbian look’: The importance of appearance norms for lesbian and bisexual women - Huxley, Caroline; Clarke, Victoria; Halliwell, Emma (Journal of Community & Applied Social Psychology, 2014)
Appearance is one way in which lesbian and bisexual identities and affiliation to lesbian, gay, bisexual (LGB) subculture can be demonstrated. ‘Butch’ and ‘androgynous’ styles have been used by lesbian women to communicate a non-heterosexual identity. However, some LGB appearance researchers have argued that there has been a mainstreaming and diversification of lesbian style in the last couple of decades, which has resulted in less distinction between lesbian and straight looks. This research draws on the Social Identity approach to explore contemporary style in lesbian and bisexual communities. Fifteen lesbian and bisexual women took part in semi-structured interviews which were analysed using thematic analysis. Although some participants reported a diversification of lesbian style, most used the term ‘butch’ to describe lesbian style, and a ‘boyish’ look was viewed as the most common contemporary lesbian style. By contrast, most participants could not identify distinct bisexual appearance norms. The data provide evidence of conflicting desires (and expectations) to visibly project social identity by conforming to specific lesbian styles, and to be an authentic, unique individual by resisting these subcultural styles
Keywords: 2000 à aujourd'hui; 2010-2019; discipline; europe; identités LGBTQIA2+; psychologie; périodes historiques; ressource en ligne; royaume-uni; régions géographiques; sciences humaines

Sexual Attitudes and Double Standards: A Literature Review Focusing on Participant Gender and Ethnic Background - Fugère, Madeleine A.; Escoto, Carlos; Cousins, Alita J.; Riggs, Matt L.; Haerich, Paul (Sexuality & Culture : An Interdisciplinary Quarterly, 2008)
We conducted a review of literature regarding sexual attitudes and double standards, focusing on participant gender and ethnic background. We found that men had more permissive sexual attitudes than women, and that African Americans had the most permissive sexual attitudes, followed by White Americans, then by Hispanic Americans and Asian Americans. The literature regarding sexual double standards was mixed; some studies showed evidence of continued sexual double standards and some studies showed the absence of sexual double standards. In some studies, men were more likely to endorse the sexual double standard than women. We found only one article addressing sexual double standards using ethnic background as a quasi-independent variable; this research revealed that non-North American (Russian and Japanese) samples were more likely to endorse the traditional double standard, that sex is more acceptable for men than for women.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amériques; approches et analyses; asie; cours; discipline; europe; japon; premier cycle; psychologie; périodes historiques; rapports sociaux de sexe; ressource en ligne; russie; régions géographiques; sciences humaines; sciences sociales; sex2283; sexisme; sexologie; sexualité; systèmes d'oppressions; thématiques; états-unis

Pornography, Women and Feminism: Between Pleasure and Politics - Ciclitira, Karen (Sexualities, 2004)
This article draws on a qualitative research study which set out to explore women’s experiences and views of pornography within the broader context of conflicting feminist positions on pornography. The research methodology posed an implicit criticism of the kind of ‘findings’ familiar from mainstream psychological research: semi-structured interviews were conducted with women from diverse backgrounds in the UK, and feminist theory and discourse analysis were used to inform interpretation of their accounts. Although the question of feminism was not explicitly raised by the interviewer, it emerged as a recurrent theme in interviews, with interviewees suggesting that the feminist anti-porn stance in particular has influenced their perspective on pornography. Their accounts show that women’s experiences are variegated, individual and complex, and that discourses of pornography and feminism may be negotiated in unpredictable ways.
Keywords: 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; féminisme pop; pornographie; premier cycle; psychologie; périodes historiques; recherche qualitative; ressource en ligne; royaume-uni; régions géographiques; sciences humaines; sex1911; sexualité; thématiques

Life with the first baby: women's satisfaction with the division of roles - Cappuccini, G.; Cochrane, R. (Journal of Reproductive and Infant Psychology, 2000)
The ways parents divide their roles after their first child is born is a particularly complex arena. The success of negotiations within this close personal relationship may be central to the future of the new family. Women and their partners were surveyed in late pregnancy and 6 months after the birth. Their attitudes to role division remained largely non-traditional after the birth, even though most of them had incorporated some traditional elements into their behaviour. Emotional support received from their partners was important to women's satisfaction with role division, which had fallen only slightly after the birth. Eight of the women were interviewed in depth to explore why it might be that satisfaction with role division tended to remain high after the birth, despite the division usually not being what they had hoped for. Contributory factors may include changes in emphasis in the division of breadwinning and the maintenance of overall responsibility for traditional role areas despite sharing of tasks.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; angleterre; approches et analyses; cours; discipline; europe; hétérosexualité; inégalités; maternité; premier cycle; privilèges; psychologie; périodes historiques; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques